PENERAPAN AKUNTANSI PERSEDIAAN BARANG DAGANG PADA UD. MUDA-MUDI TOLITOLI - Karongkong, Kenny Regina; Ilat, Ventje; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2018)
In trading company, inventory is a valuable resource as it become the larger asset than current asset. It because the primary income of the company coming from selling goods from inventory. Therefore, accounting management for the inventory is important to avoid fraud. The data for This paper is provided by a distributor company that provide a basic needs for the consumer to implement an accountable inventory management. The Object of this paper is a company name UD. Muda-Mudi Tolitoli. This paper is using a Deskriptif-Kualiatif method. This Paper conclude that UD. Muda-Mudi has implemented accountable based for their inventory management but still need an improvement about providing a division workload for entry and saving goods and income.Keyword : inventory, deskriptif kualitatif